Independent prognostic significance of tissue and circulating microrna biomarkers in hepatocellular carcinoma - Long-Bin Jeng; Wen-Ling Chan; Chiao-Fang Teng (Discover Oncology)
Abstract Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide. Although many therapeutic modalities have been established for treating HCC patients, the outcomes of patients remain unsatisfactory. Development of independent prognostic biomarkers is thus an important need to allow for early diagnosis and timely treatment. MicroRNAs (miRNAs) are the most studied class of small non-coding RNAs. It has been shown that miRNAs play essential roles in the multiple steps of HCC tumorigenesis and progression. Furthermore, the baseline expression levels of many miRNAs are altered in tumor tissues and blood circulation of HCC patients. Therefore, miRNAs have emerged as independent biomarkers for the prediction of HCC prognosis. This review provides a comprehensive literature-based summary of tissue and circulating miRNA biomarkers with independent prognostic significance in HCC.